KEARIFAN LOKAL MASYARAKAT DESA SEKITAR DANAU BEKAT DALAM MENJAGA KELESTARIAN DI KECAMATAN TAYAN HILIR KABUPATEN SANGGAU Local Wisdom Villagers Around The Bekat Lake Is A Blessing In Preserving In Subdistricts Tayan Hilir In Districts Sanggau - Simangunsong, Jhon Mayer; kandar, Is; Darwati, Herlina (Universitas Tanjungpura, 2014)
This study aims to determine the form of local wisdom and knowledge about how to transfer indigeneous communities surrounding villages in preserving in subdistricts Tayan Hilir and districts Sanggau. The method used is descriptive qualitative. Collecting data on the respondens consisted of 55 people from Pedalaman rural communities with other respondents from rural communities Emberas amounting to 23 people. Data collections techniques using observations, deep interview, and documentation by using cameras and voice recorders. Based on the research result, obtained by form local wisdom people among others are â€œUmpan Danauâ€ tradition, polluting the lakes Bekat ban, the ban made sources of fire in the lake area Bekat, ban on felling of trees in the lake area blessing, prohibition of taking or killing of protected animals in the lake Bekat areaâ€™s, prohibition of taking fish with destructive methods, the agreement using traditional fishing gear, restrictionÂ on the use of fishing gear such as jermals, an agreement limiting the number of fish catches, restrictions on the types of fish that may be taken, prohabition of taking protected fishcommunity, the rules and fees for the outside community in taking fish, as well as maintaining an atitude and said words. How to transfer the knowledge of indigeneous villager fromÂ rural communities Pedalaman in conserving Bekats lake is through direct experience in the field in everyday life for example, following the costumary tradition every year, immediately following the experience of parents looking for fish, and the socialization of the government in managing the Bekatâ€™s lake. Key Words: Local wisdom, indigeneous, Bekatâ€™s Lake